Independence and Interdependence Predict Health and Wellbeing: Divergent Patterns in the United States and Japan - Kitayama, Shinobu; Karasawa, Mayumi; Curhan, Katherine B.; Ryff, Carol D.; Markus, Hazel R. (Frontiers in Psychology, 2010)
A cross-cultural survey was used to examine two hypotheses designed to link culture to well-being and health. The first hypothesis states that people are motivated toward prevalent cultural mandates of either independence (personal control) in the United States or interdependence (relational harmony) in Japan. As predicted, Americans with compromised personal control and Japanese with strained relationships reported high perceived constraint. The second hypothesis holds that people achieve well-being and health through actualizing the respective cultural mandates in their modes of being. As predicted, the strongest predictor of well-being and health was personal control in the United States, but the absence of relational strain in Japan. All analyses controlled for age, gender, and personality traits. The overall pattern of findings underscores culturally distinct pathways (independent versus interdependent) in achieving these positive life outcomes.